Using Self-Experimentation and Single-Subject Methodology to Promote Critical Thinking - Brian J. Cowley, PhD, BCBA; Ann Lindgren; David Langdon (Park University, 2006)
Critical thinking is often absent from classroom endeavor because it is hard to define (Gelder, 2005) or is difficult to assess (Bissell & Lemons, 2006). Critical thinking is defined as application, analysis, synthesis, and evaluation (Browne & Minnick, 2005). This paper shows how self-experimentation and single-subject methodology can be used to promote many levels of critical thinking in an Applied Behavior Analysis course. Two classroom assignment examples of this process and a grading rubric are provided.